2016
DOI: 10.1172/jci84456
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages sustain HIV replication in vivo independently of T cells

Abstract: Macrophages have long been considered to contribute to HIV infection of the CNS; however, a recent study has contradicted this early work and suggests that myeloid cells are not an in vivo source of virus production. Here, we addressed the role of macrophages in HIV infection by first analyzing monocytes isolated from viremic patients and patients undergoing antiretroviral treatment. We were unable to find viral DNA or viral outgrowth in monocytes isolated from peripheral blood. To determine whether tissue mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(240 citation statements)
references
References 72 publications
(108 reference statements)
7
227
0
6
Order By: Relevance
“…As is discussed below, recovery only fails when the size of the latent reservoir is substantially reduced (44, 109111). Controversy remains over the question of whether other cell types including macrophages serve as stable HIV-1 reservoirs (112123). To date, long term persistence of replication-competent HIV-1 in the setting of optimal ART has only been demonstrated for resting CD4 + T cells (124).…”
Section: Evidence For Latent Infection Of Resting Memory Cd4+ T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is discussed below, recovery only fails when the size of the latent reservoir is substantially reduced (44, 109111). Controversy remains over the question of whether other cell types including macrophages serve as stable HIV-1 reservoirs (112123). To date, long term persistence of replication-competent HIV-1 in the setting of optimal ART has only been demonstrated for resting CD4 + T cells (124).…”
Section: Evidence For Latent Infection Of Resting Memory Cd4+ T Cellsmentioning
confidence: 99%
“…This may in part reflect the difficulty of sampling tissue macrophages, particularly in sites such as the central nervous system. Persistence in tissue macrophages can in principle be studied in novel humanized mouse models (123) and in the SIV model, but only through the use of animals on fully suppressive, long term ART and with the caveat that restriction by SAMHD1 is counteracted by SIV Vpx (68, 69). …”
Section: Evidence For Latent Infection Of Resting Memory Cd4+ T Cellsmentioning
confidence: 99%
“…Moreover, in patients exposed to antiretroviral therapies, HIV-1-infected macrophages may maintain a constant viral production due in part to the low doses of antiviral drugs that reach the tissues (7). In addition, macrophages are now recognized as able to sustain viral replication, transmission, and persistence even in the absence of CD4 ϩ T cells in vivo (8) and under antiretroviral therapy (9). Thus, macrophages represent an important viral reservoir even in patients under antiretroviral therapy (3).…”
mentioning
confidence: 99%
“…Monocytes that express CD16 are more prone to infection with HIV-1 in vitro, and some studies have found very low levels of viral DNA within these cells after flow cytometric sorting from peripheral blood of HIV-infected individuals (80,81). However, other groups have reported that viral DNA is not detectable in peripheral blood monocytes from HIV-infected individuals (82,83).…”
Section: Evidence That Macrophages Support Viral Replicationmentioning
confidence: 99%
“…In this model, immunodeficient mice were reconstituted with fetal, human, hematopoietic cells that developed into myeloid cells but not T cells. These particular "humanized" mice, termed myeloid-only mice (MoM), could subsequently be infected with macrophage-tropic strains of HIV in vivo and support viral replication (83). Interestingly, very few CCR5-tropic viruses were able to replicate in MoM, suggesting this might be a very rare event in vivo.…”
Section: Animal Models Of Macrophage Infection In Vivomentioning
confidence: 99%